The Influence of Communication and Innovation Ability on Member Participation and Management Performance from Organizational Aspects in Consumer Cooperatives in Pekanbaru City - Riani, Lisa; Machasin, Machasin; Garnasih, Raden Lestari (CV. Rayyan Dwi Bharata, 2025)
This research aims to find out whether communication and the ability to innovate influence member participation and management performance in consumer cooperatives in Pekanbaru City. This research was conducted by distributing research questionnaires to 10 active consumer cooperatives in Pekanbaru City with a total of 30 respondents. Hypothesis testing uses the SEM-PLS statistical test tool. The research results show that communication has a positive effect on member participation, the ability to innovate has no effect on member participation, communication has no effect on management performance, the ability to innovate has a positive effect on management performance, indirectly communication through member participation has a positive and significant effect on management performance, Indirectly, the ability to innovate through member participation has no influence on the performance of cooperative management.